Osteomielitis vertebral por Candida parapsilosis, reporte de un caso y revisión bibliográfica - Maureira E., Valeria; Pérez-Luco A., Tomás; López F., Valentín; Olivares C., Roberto; Ávila O., Fernanda (Revista Hospital Clínico Universidad de Chile, 2017)
Invasive candidiasis is a pathology associated with known risk factors. In the past decades its incidence has increased, due to an increment in new non-albicans species, one of which is Candida parapsilosis. The most frequent presentation still is candidemia, however, candidial osteomyelitis cases have been described, usually compromising the axial skeleton. In this article, we report a case of candida parapsilosis spondylodiscitis, along with a review of the published literature of the subject.